Clinical Association of Anti-TPO in Patients with Chronic Urticaria (Journal of Rangpur Medical College, 2023)
Background: Chronic urticaria may occur when the body's immune system attacks its self-tissues. It is a skin condition marked by brief purpuric wheals that last longer than six weeks. Uncertainty surrounds the disease's etiopathogenesis. Autoimmunity and endocrine dysfunction may both be at play, according to the available research.Objective: This study aimed to evaluate if thyroid immunity is statistically linked with chronic urticaria.Methods: This case-control study was held from June 2022 to March 2023 at Department of Dermatology & Venerology in IMCH, Popular diagnostic center and Digital Hospital in Gazipur. We examined the prevalence of autoantibodies (Anti-TPO) in 50 chronic urticaria patients and 50 healthy volunteers. In all participants, thyroid hormone and thyroid auto-antibodies were assessed.Results: Thyroid function abnormalities were found 7 (13.42%) patients and Anti-TPO is positive in 38(76%) patients respectively. Only 2 (4%) of the individuals in the control group had positive anti-TPO tests. With chronic urticaria, anti-TPO levels were considerably greater (P 0.05) than in the control group.Conclusions: This study shows a significant association between chronic urticaria and thyroid auto-immunity. The test is conducted to detect thyroid auto-antibodies is relevant in patients with chronic urticaria.J Rang Med Col. September 2023; Vol. 8, No. 2: 29-33